PENGUJIAN APLIKASI ABSENSI KARYAWAN BERBASIS WEB MENGGUNAKAN METODE SPIRAL PADA PT POWER STEEL MANDIRI KABUPATEN TANGERANG - Euis Syania Khafiffach; Fahrul Aji Kurniawan; rasyid, faisal; Muhammad Riswan; Aries Saifudin (CV. Shofanah Media Berkah, 2023)
Testing this employee attendance application aims to play an important role in ensuring the reliability and performance of the system at PT. SELF POWER STEEL. By adopting the abstract approach described in this study, application developers and owners can identify and fix potential problems before the application is widely used by company employees. Testing employee attendance applications is an important process in the development and implementation of a system that can monitor employee attendance and activity in a company. In the fast-paced modern business environment, the use of employee attendance apps is becoming more common as an effective tool for managing employee attendance. In this study, we describe an abstract approach for testing employee attendance applications designed to verify the performance, reliability and functionality of the application. Testing an employee attendance application involves a series of test steps designed to identify potential problems or defects in the system